Using Repeated Readings to Support Fluency and Comprehension - Wymer, Julie (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2022)
A critical component of early literacy is fluency. Reading with fluency in early elementary school allows a student to find success in future reading. A student who cannot read fluently will have a limited understanding of the text. This manuscript addresses the importance of developing fluency and using repeated readings to develop this skill, and in turn, build comprehension. Through repeated readings, students build fluency with meaningful reading experiences. Studies show that repeated readings help students improve their reading at a rate that supports comprehension. Repeated readings are an effective instructional strategy used in the primary classroom to develop fluency (the ability to read with appropriate rate, accuracy, and expression) and reading comprehension (the ability to understand the text).